Motif Perilaku Begal Sepeda Motor Di Kota Bekasi : Studi Literatur Review - Dimas Guntur Wicaksono; Ivan Maulana Ibrahim; Rajif Fadillah Muhammad; Ricard Novan Marbun; Putri Nur Ramadhani; Mic Finanto Ario Bangun (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The motives for motorbike robbery behavior in Bekasi have become a significant concern in recent years. The research results show that economic, social and cultural factors have an important role in influencing motorbike theft. This research shows that motorbike theft in Bekasi occurs more often in areas with high levels of poverty and low levels of education. The method in this research uses the literature study method. Apart from that, research also reveals that motorbike theft in Bekasi is mostly carried out by individuals who have criminal records and are involved in criminal organizations. Based on the research results, the government and society should make efforts to increase public awareness of the importance of protecting motorbikes and improving people's quality of life. to reduce motorbike theft in Bekasi